Intensive monitoring in Portugal : a pharmacy-based model to assess in real-life conditions : the example of new glucose lowering drugs - Torre, Carla (2017)
Tese de doutoramento, Farmácia (Farmacoepidemiologia), Universidade de Lisboa, Faculdade de Farmácia, 2018